2017
DOI: 10.1111/jfpe.12560
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of color changes of popped rice during microwave popping: Effect of salt and moisture content

Abstract: Paddy, coated with a dielectric salt was popped using microwave energy. The kinetics of color changes of the popped rice with the variation of heating time (0–60 s), sample moisture content (12–18% wb), and level of salt coating (0–5% w/w) were studied. The parameters, estimating the change in color of the popped rice, were measured in terms of L*, a*, b* color coordinate system using a Chroma‐meter. The total color change (ΔE*), chroma (C*), hue angle (H*), and browning index (BI*) were estimated from these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…In the case of sand‐bed puffing, salt content beyond 4% level showed insignificant effect ( p > .05; vide Figure b). Similar finding was also observed by Devi and Das () in microwave popping of paddy at different levels of salt coating. Effect of preconditioning temperature on the WI was insignificant ( p > .05) for microwave puffed brown rice, while this was found to be highly significant ( p < .001) with positive linear term and negative quadratic ( p < .05) terms for sand bed puffing.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…In the case of sand‐bed puffing, salt content beyond 4% level showed insignificant effect ( p > .05; vide Figure b). Similar finding was also observed by Devi and Das () in microwave popping of paddy at different levels of salt coating. Effect of preconditioning temperature on the WI was insignificant ( p > .05) for microwave puffed brown rice, while this was found to be highly significant ( p < .001) with positive linear term and negative quadratic ( p < .05) terms for sand bed puffing.…”
Section: Resultssupporting
confidence: 89%
“…Salt improves thermal conductivity and dielectric loss factor of rice kernel. The former helps puffing using sand-bed and the latter helps in puffing using microwave energy (Devi & Das, 2017;Arnaud, 1963;Hoke et al, 2005;van der Sman & Bows, 2017). Additionally, preconditioning process makes the kernel surface hard and compact with starch-salt interaction (Das et al, 2015;Mohapatra, 2010).…”
Section: Expansion Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of the linear term of each factor indicated that yellowness increased when the IMC decreased and when MWP and PT increased, as shown in Figure . When the IMC increased, the yellowness value decreased (Devi & Das, ). The experiment was also showed that increasing the heating time might increase brownness in popped rice.…”
Section: Resultsmentioning
confidence: 99%
“…Kinetics studies are generally used to study the color changes in fruits and vegetables, such as chestnuts [21], grapes [22], and rice [23]. The zero-or first-order reaction is suitable for most kinetic analyses, which are mostly applied in the food industry [24].…”
Section: Introductionmentioning
confidence: 99%